ANALISIS KEMAMPUAN HIGHER ORDER THINGKING SKILLS (HOTS) PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA KURIKULUM MERDEKA - Netriwati; Anggraini, Fitria; Niatapia, Susi; Cahayanti, Adinda Zein; Safitri, Shanria; Nendra, Fadly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to examine how students use HOTS Higher Order Thinking Skills (HOTS) when learning mathematics using the Independent Curriculum.